Dispositif type relatif aux mesures du ressort de l'état du port dans le contexte de la lutte contre la pêche illicite, non déclarée et non réglementée (Rome, 2007)
This model scheme is addressed to all states, fishing entities, and regional fisheries management organizations. Its purpose is to facilitate the implementation of effective action by port states to prevent, deter and eliminate illegal, unreported and unregulated fishing. The publication includes a CD-ROM on port state measures.--Publisher's description.
Keywords: Fishery management, international,Fishery law and legislation,Fisheries,Quản lý thuỷ sản quốc tế,Pháp luật và pháp luật về thủy sản,Thủy sản; International cooperation,Hợp tác quốc tế